The Chinese question : ethnicity, nation, and region in and beyond the Philippines - Hau, Caroline S., 1969- (Kyoto CSEAS series on Asian studies, 2014)
As the meanings of "Chinese" and "Filipino" evolve, intractable contradictions are appearing in the concepts of citizenship and national belonging. Through an examination of cinematic and literary works, The Chinese Question shows how race, class, ideology, nationality, territory, sovereignty, and mobility are shaping the discourses of national integration, regional identification, and global cosmopolitanism.